Representation of Linguistic Differentiation in the "Word-Formation Dictionary of the Russian Language" by A.N. Tikhonov (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides a brief overview of research on the theory of the word-formation nest in linguistics, addresses the issue of semantic space and the vertices of the word-formation nest. It also describes how the phenomenon of linguistic differentiation is reflected in the "Word-formation dictionary of the Russian language" by A.N. Tikhonov.